Electrocardiogram abnormalities and prognosis in COVID-19 - Chevrot, Gabriel; Hauguel-Moreau, Marie; Pépin, Marion; Vieillard-Baron, Antoine; Lot, Anne-Sophie; Ouadahi, Mounir; Hergault, Hélène; Aïdan, Vincent; Greffe, Ségolène; Costantini, Adrien; Dubourg, Olivier; Beaune, Sébastien; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: COVID-19 is a major pandemic with potential cardiovascular complications. Few studies have focused on electrocardiogram (ECG) modifications in COVID-19 patients. Method and results: We reviewed from our database all patients referred to our hospital for COVID-19 between January 1st, 2020, and December 31st, 2020: 669 patients were included and 98 patients died from COVID-19 (14.6%). We systematically analyzed ECG at admission and during hospitalization if available. ECG was abnormal at admission in 478 patients (71.4%) and was more frequently abnormal in patients who did not survive (88.8% versus 68.5%, p < 0.001). The most common ECG abnormalities associated with death were left anterior fascicular block (39.8% versus 20.0% among alive patients, p < 0.001), left and right bundle branch blocks (p = 0.002 and p = 0.02, respectively), S1Q3 pattern (14.3% versus 6.0%, p = 0.006). In multivariate analysis, at admission, the presence of left bundle branch block remained statistically related to death (OR = 3.82, 95% confidence interval [CI]: 1.52-9.28, p < 0.01), as well as S1Q3 pattern (OR = 3.17, 95% CI: 1.38-7.03, p <0.01) and repolarization abnormalities (OR = 2.41, 95% CI: 1.40-4.14, p < 0.01). On ECG performed during hospitalization, the occurrence of new repolarization abnormality was significantly related to death (OR = 2.72, 95% CI: 1.14-6.54, p = 0.02), as well as a new S1Q3 pattern (OR = 13.23, 95% CI: 1.49-286.56, p = 0.03) and new supraventricular arrhythmia (OR = 3.8, 95% CI: 1.11-13.35, p = 0.03). Conclusion: The presence of abnormal ECG during COVID-19 is frequent. Physicians should be aware of the usefulness of ECG for risk stratification during COVID-19.